2022
DOI: 10.2147/cmar.s362858
|View full text |Cite
|
Sign up to set email alerts
|

Transformation from Small Cell to Squamous Cell Carcinoma in a Thymic Carcinoma Patient with a Durable Response to Anlotinib: A Case Report

Abstract: The most common pathologic type of thymic carcinoma (TC) is squamous cell carcinoma (SCC). Small cell carcinoma is relatively rare, accounting for approximately 2% to 5% of all thymic tumors. Histologic transformation of TC has not yet been reported. Available treatments for TC patients who progress after first-line therapy are limited, which contributes to their poor prognosis. We reported an extraordinary case of a 66-year-old man who was diagnosed with thymic small cell carcinoma that transformed into SCC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Abnormalities or dysfunctions in these pathways might be potential mechanisms for SCLC-to-SCC transformation. Additionally, a case report [ 28 ] has found a transformation from small cell to SCC in a thymic carcinoma patient, suggesting that although SCLC-to-SCC transformation is rare, it is possible to transform SCLC into SCC. Others could not infer the transformation mode (Additional file 1 : Figure S7G).…”
Section: Resultsmentioning
confidence: 99%
“…Abnormalities or dysfunctions in these pathways might be potential mechanisms for SCLC-to-SCC transformation. Additionally, a case report [ 28 ] has found a transformation from small cell to SCC in a thymic carcinoma patient, suggesting that although SCLC-to-SCC transformation is rare, it is possible to transform SCLC into SCC. Others could not infer the transformation mode (Additional file 1 : Figure S7G).…”
Section: Resultsmentioning
confidence: 99%
“…Zuo et al reported that an advanced TC patient who had previously received multi-line therapy, including chemotherapy, radiotherapy, and antiangiogenic therapy, achieved over 23 months of PFS and six years of OS with anlotinib treatment, and the adverse reactions were mild and tolerable [ 20 ]. Qin et al reported that a thymic small cell carcinoma patients who transformed into squamous cell carcinoma after failure of multi-line therapy received anlotinib as fourth-line [4 th -line] therapy and achieved a PFS of 25 months and an OS of 10 years, the tolerance was well [ 21 - 27 ]. These two case reports suggest that anlotinib may be a promising treatment strategy for patients with T and TC after failure of multi-line therapy.…”
Section: Introductionmentioning
confidence: 99%